LEVEL OF KNOWLEDGE OF SENIOR HIGH SCHOOL STUDENTS TO NORTH COASTAL OF JAVA CONSERVATION: Fahmi Arif Kurnianto, Bejo Apriyanto , Elan Artono Nurdin , Fahrudi Ahwan Ikhsan - Fahmi Arif Kurnianto; Bejo Apriyanto; Elan Artono Nurdin; Fahrudi Ahwan Ikhsan (Department of Geography Education, University of Jember, 2017)
The purpose of this study to analysis the influence of group investigation learning model towards the level of conservation knowledge of students in senior high school. The type of research is the quasi-experimental study with nonequivalent control group posttest only design. The subject of the study consisted of class XI Social Science are selected based on the score of Final Semester Exam on 2014-2015 teachings year that had an average of almost the same (homogeneous).The results of this study are showed significant influence of GI models on Geography level of knowledge to learn of students. It was based on the results of the Independent Sample T-Test analysis showed a p-value of 0.000 level. P-level value is smaller than 0.05 (p <0.05). Keywords: Group Investigation Learning, Level of knowledge, conservation References Huda, Miftahul. 2011. Cooperative Learning. Yogyakarta: Pustaka Pelajar. Jacksen, Sherri L. 2011. Research Methode: Moduler Approach. Stamford: Cengage Learning. Majid, Abdul. 2013. Strategi Pembelajaran. Bandung : PT Remaja Rosdakarya. Mushodik. 2013. Pengaruh Model Pembelajaran Group Investigation terhadap Kemampuan Berpikir Kritis Siswa Madrasah Aliyah Negeri 6 Jakarta. Tesis tidak diterbitkan. Malang: PPS Universitas Negeri Malang. Rusman. 2012. Model-Model Pembelajaran. Jakarta: Raja Grafindo Persada. Sharan, Shlomo. 2014. Handbook of Cooperative Learning. New York: Teachers College Press. Slavin, Robert E. 2005. Cooperative Learning: theory, research and practice (N. Yusron. Terjemahan). London: Allymand Bacon. Buku asli diterbitkan tahun 2005. Sumarmi. 2012. Model-Model Pembelajaran Geografi. Malang : Aditya Media Publishing. Tan, Ivy Geok Chin. 2004. Effects of cooperative learning with group investigation on secondary students’ achievement, level of knowledge and perceptions. Singapore: National Institute of Education. Trianto. 2007. Model-model Pembelajaran Inovatif Berorientasi Konstruktivistik. Jakarta: Prestasi Pustaka. Copyright (c) 2017 Geosfera Indonesia Journal and Department of Geography Education, University of Jember Copyright Notice This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License